1999
DOI: 10.1074/jbc.274.45.32376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Molecular Mechanism for the Antagonistic Action of a Novel 1α,25-Dihydroxyvitamin D3 Analogue toward Vitamin D Receptor Function

Abstract: 5). The effects exerted via the VDR are called genomic effects, in contrast to non-genomic effects, which means that 1␣,25(OH) 2 D 3 acts within a short period without transcription of target genes (6). The VDR-mediated effects of 1␣,25(OH) 2 D 3 in vivo are well known, since there is a human disease associated with the abnormality of the VDR gene, which is called vitamin D dependence type II (7). In addition, a mouse model of the disease was generated by targeting the VDR gene and has been used the analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…Only recently an antagonist that blocks VDR-mediated actions of 1,25(OH)2D3 has been described [45,46]. Whether this antagonist, could also block the detected 1,25(OH)2D3-induced increase in IR expression and insulin action remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently an antagonist that blocks VDR-mediated actions of 1,25(OH)2D3 has been described [45,46]. Whether this antagonist, could also block the detected 1,25(OH)2D3-induced increase in IR expression and insulin action remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These are the (23S)-and (23R)-25-dehydro-1α-hydroxyvitamin D 3 -26,23-lactones (TEI-9647 and TEI-9648, respectively) [4][5][6], the 25-carboxylic ester derivatives of 1α,25-(OH) 2 D 3 (ZK159222 and ZK168281) [7,8], and the (23S,25S)-N-benzyl-1α, 25- [4,6,12]. Moreover, we demonstrated that TEI-9647 prevents heterodimer complex formation between the VDR and retinoid X receptor (RXR), and recruitment of steroid receptor coactivator-1 (SRC-1) to VDR [13].…”
Section: Introductionmentioning
confidence: 92%
“…In 1999, studies on the modification of the side-chain structure-based on a 1a,25-dihydroxyvitamin D 3 -26,23-lactone metabolite [31,32] derived from 1-led to the discovery of TEI-9647 (5) and TEI-9648 (6) (Scheme 4). [33][34][35][36][37][38][39] These two vitamin D 3 analogues, each containing an a-methylene-g-butyrolactone component in the side chain, are the first specific antagonists of VDR-mediated genomic action of 1: analogue 5, with the (23S) configuration, displays stronger antagonism than 6, with the (23R) configuration. The other class of antagonists is that of ZK-159222, which possesses long CD-ring side chains that include cyclopropane rings in their middles (see Section 5, Scheme 19).…”
Section: ]-Rxr Complex and This Complex Binds Tomentioning
confidence: 99%